Tuning the micromorphology and exposed facets of MnOx promotes methyl ethyl ketone low-temperature abatement: boosting oxygen activation and electron transmission. Issue 15 (10th July 2018) - Jian, Yanfei; Ma, Mudi; Chen, Changwei; Liu, Chao; Yu, Yanke; Hao, Zhengping; He, Chi
Abstract : MnO x nanowires with highly exposed 101 facets of Mn3 O4 possess excellent low-temperature activity and stability for methyl ethyl ketone destruction. Abstract : MnO x oxides with different morphologies (nanowire (MnO x -W), nanocube (MnO x -C), nanorod (MnO x -R), and nanosphere (MnO x -S)) and exposed facets were synthesized via a solvothermal method. The catalytic performance of the synthesized MnOx materials for methyl ethyl ketone (MEK) destruction was investigated. Results show that the activity of MnO x -W with highly exposed 101 facets of Mn3 O4 is superior to that of MnO x -C, MnO x -R, and MnO x -S exposing 321 facets of Mn2 O3, 110 facets of MnO2, and 101 and 112 facets of Mn3 O4, respectively. MEK can be completely mineralized into CO2 at 195 °C over MnO x -W under a relatively high gas hourly space velocity of 37 200 h −1, which is even better than some typical noble metal loaded catalysts. The lowest apparent activation energy of MnO x -W (27.7 kJ mol −1 ) for MEK destruction also confirms its excellent catalytic activity. Density functional theory (DFT) results reveal that the 101 facets of Mn3 O4 have the highest MEK adsorption energy (0.79 eV), which indicates that MEK molecules have a high affinity to adsorb onto the MnO x -W surface, promoting the oxidation process of MEK. In situ DRIFTS and TPSR results indicate that the mineralization of MEK into CO2 over MnO x -W goes through an oxidation route with diacetyl as the primary intermediate. We found that the highly exposed 101 active facets, abundant oxygen vacancies, and excellent low-temperature reducibility are responsible for the superior oxidation performance of MnO x -W. This finding may bring new insights into the designing of highly effective catalysts and has implications for a wide range of reactions not limited to MEK oxidation.